Index of authors & scholars - The Editors, - (Nordic Archaeological Abstracts - NAA, 1989)
The alphabet employed is a b c ... u v w x y (ti) z å aa a (æ) 6 (ø). Finnish, German and Greenlandic names with aa are, however, alphabetized as with a double a. German a, 6 and ti are treated as Nordic a, 6 and y; i and j, v and w are separated. Icelandic o and p are treated as d and th. Other diacritic signs are not taken into consideration. The cyrillic alphabet is transliterated according to the international system for the transliteration of Cyrillic characters [ISO].